2012
DOI: 10.1007/s11149-012-9196-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal monitoring of credit-based emissions trading under asymmetric information

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It further points out that for many developing countries, although the implementation of environmental policies is weak, the tradable pollution permits would be a more viable policy option. Third, on the enterprise project level, MacKenzie and Ohndorf [26] extend the general framework of incomplete policy implementation in order to examine the special characteristics of credit-based emission trading mechanism (e.g., clean development mechanism). According to the emission reduction cost and penalty scheme, the optimal supervision of credit-based systems is usually discontinuous, which is significantly different from that of cap-and-trade scheme and environmental tax system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It further points out that for many developing countries, although the implementation of environmental policies is weak, the tradable pollution permits would be a more viable policy option. Third, on the enterprise project level, MacKenzie and Ohndorf [26] extend the general framework of incomplete policy implementation in order to examine the special characteristics of credit-based emission trading mechanism (e.g., clean development mechanism). According to the emission reduction cost and penalty scheme, the optimal supervision of credit-based systems is usually discontinuous, which is significantly different from that of cap-and-trade scheme and environmental tax system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results also highlighted the relative importance of adverse selection and moral hazard. To facilitate effective supervision/monitoring of emission reduction, Mackenzie and Ohndorf [17] extended the general framework on incomplete enforcement of policy instruments to reflect the particularities of credit-based mechanisms under asymmetric information. The results indicated that, depending on the actual abatement cost and penalty schemes, optimal monitoring for credit-based systems is often discontinuous and differs significantly from those applied for cap-and-trade schemes or environmental taxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…27 With abatement being imperfectly observable, however, firms have an incentive to misreport their actual emissions/abatement, which has been shown to be a considerable issue without appropriate enforcement mechanisms (see, e.g., Gray and Shimshack 2011;Telle 2013). The incentive for false reporting, however, is likewise present under any other policy instrument such as emission taxes or different forms of emissions trading (see, e.g., Harford 1978;Malik 1992;Heyes 2000;Macho-Stadler and Perez-Castrillo 2006;MacKenzie and Ohndorf 2012b). In fact, one can show that under such schemes this problem may be even more pronounced than for standards stipulated via benchmarking: whereas under benchmarking regulation, increased monitoring effort strictly decreases misreporting, this is not the case for emission taxes (see, e.g., Stranlund et al 2009).…”
Section: Applicability Of Benchmarking Regulationmentioning
confidence: 99%